2022
DOI: 10.3346/jkms.2022.37.e265
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report for Acute Myopericarditis After NVX-CoV2373 (Novavax®) COVID-19 Vaccination

Abstract: Post-vaccination myocarditis after administration of the NVX-CoV2373 coronavirus disease 2019 (COVID-19) vaccine has been reported in a limited population. We report the first biopsy-proven case of myopericarditis after administration of second dose of NVX-CoV2373 COVID-19 vaccine (Novavax®) in Korea. A 30-year-old man was referred to emergency department with complaints of chest pain and mild febrile sense for two days. He received the second dose vaccine 17 days ago. Acute myopericarditis by the vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…They reported four suspected cases of myocarditis, but no confirmation of cases was described. Korean authors also published a case report of a 30 yearold male with clinically confirmed myocarditis onset 17 days post dose 2 Nuvaxovid as a vaccination complication [32].…”
Section: Discussionmentioning
confidence: 99%
“…They reported four suspected cases of myocarditis, but no confirmation of cases was described. Korean authors also published a case report of a 30 yearold male with clinically confirmed myocarditis onset 17 days post dose 2 Nuvaxovid as a vaccination complication [32].…”
Section: Discussionmentioning
confidence: 99%
“… 69 In a case-control study, CoronaVac’s myopericarditis rate was not higher than controls, in contrast to BNT162b2’s rate that exceeded controls after dose 2 and for doses 1 and combined 69 ( Table S1 ). For NVX-CoV2373/Nuvaxoid recombinant S1 protein vaccine, there is a case report of myocarditis after administration, 74 and myocarditis was also reported in 4 cases out of 40 000 vaccine recipients in Phase III trials where it occurred only in men and within 10 days of vaccine receipt. 75 Novavax released a statement June 3, 2022, that the rate of myocarditis was balanced between the vaccine and placebo arms (0.007% and 0.005%), and there is insufficient evidence to establish a causal relationship.…”
Section: Sars-cov-2 Vaccine-associated Myocarditis and Myocardial Injurymentioning
confidence: 99%
“…5,6 Few cases of acute myocarditis have been reported in association with the protein-based subunit COVID-19 vaccinations. 7,8 Here, we report a case series involving 11 patients who developed symptoms of myocarditis after receiving the Taiwanapproved COVID-19 vaccination and fulfilled the imaging diagnostic criteria confirmed by cardiovascular magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%